An Act for the More Effectual Suppression of Drinking Houses and Tippling Shops, in Acts & Resolves of the General Assembly of the State of Rhode Island (1853). - (:unkn) unknown (My University, 1853)
§ 10: "It shall be the duty of any mayor, alderman, city marshal, city or town sergeant, constable or police officer, of any city or town, if he shall have information that any ale, wine, rum, or other strong or malt liquors, or any mixed liquors as aforesaid, are kept for sale or sold in any tent, shanty, hut or place of any kind for selling refreshments in any public place, on or near the ground of any cattle show, agricultural exhibition, military muster or public occasion of any kind, to search such suspected place
Keywords: ARMED FORCES